Algorithms - ESA 2015 : 23rd Annual European Symposium, Patras, Greece, September 14-16, 2015, Proceedings - Bansal, Nikhil; Finocchi, Irene; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 23rd Annual European Symposium on Algorithms, ESA 2015, held in Patras, Greece, in September 2015, as part of ALGO 2015. The 86 revised full papers presented together with two invited lectures were carefully reviewed and selected from 320 initial submissions: 71 out of 261 in Track A, Design and Analysis, and 15 out of 59 in Track B, Engineering and Applications. The papers present real-world applications, engineering, and experimental analysis of algorithms.
Keywords: Logic design; Computer science; Computational complexity; Software engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Discrete Mathematics in Computer Science; Software Engineering; Mathematical Logic and Formal Languages